2017
DOI: 10.1016/j.phrs.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of mitochondrial quality control in peripheral artery disease: New therapeutic opportunities

Abstract: Peripheral artery disease (PAD) is a multifactorial disease initially triggered by reduced blood supply to the lower extremities due to atherosclerotic obstructions. It is considered a major public health problem worldwide, affecting over 200 million people. Management of PAD includes smoking cessation, exercise, statin therapy, antiplatelet therapy, antihypertensive therapy and surgical intervention. Although these pharmacological and non-pharmacological interventions usually increases blood flow to the ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 135 publications
(161 reference statements)
0
14
0
1
Order By: Relevance
“…Our results indicate that simvastatin prevented Ang II-induced severe mitochondrial swelling and vacuolization. In addition, simvastatin maintained mitochondrial length and dynamics through mitochondrial quality regulation (Ueta, Gomes, Ribeiro, Mochly-Rosen, & Ferreira, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Our results indicate that simvastatin prevented Ang II-induced severe mitochondrial swelling and vacuolization. In addition, simvastatin maintained mitochondrial length and dynamics through mitochondrial quality regulation (Ueta, Gomes, Ribeiro, Mochly-Rosen, & Ferreira, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Over the last decade, several studies have demonstrated that changes in mitochondrial function are critical to induce exercise benefits in heart failure [195]. Overall, exercise training improves the efficiency of mitochondrial oxidative phosphorylation [68], reduces mitochondrial permeability transition [68], increases the mitochondrial clearance of toxic molecules including ROS and aldehydes [196,197] and increases mitochondria number, size and clearance [68] in heart failure. In this context, exercise training would improve left ventricular function in heart failure animals by reestablishing mitochondrial functionality.…”
Section: Exercise and Mitochondrial Dysfunction In Heart Failurementioning
confidence: 99%
“…Under physiological conditions, fusion and fission processes are balanced [6, 7]. However, under certain pathological conditions, the fission process is increased and the excessive mitochondrial fission promotes the disease progression; for instance, the mitochondrial fission increases in endothelial cells in diabetic states and in pulmonary artery smooth muscle cells in pulmonary arterial hypertension, and the increased mitochondrial fission contributes to the impairment of endothelial function in diabetes and hyperproliferation of pulmonary artery smooth muscle cells in pulmonary arterial hypertension [8, 9].…”
Section: Introductionmentioning
confidence: 99%